Evaluation of Different Dentifrice Compositions for Increasing the Hardness of Demineralized Enamel: An in Vitro Study - Pedro Henrique Cabral Oliveira; Marcia Regina Cabral Oliveira; Luiz Henrique Cabral Oliveira; Ravana Angelini Sfalcin; Marcelo Mendes Pinto; Ellen Perin Rosa; Alessandro Melo Deana; Anna Carolina Ratto Tempestini Horliana; Paulo Francisco César; Sandra Kalil Bussadori (MDPI AG, 2019)
This study aimed to evaluate microhardness of a dentifrice containing fluoride and arginine compared to a positive control (fluoride only) and a negative control (no fluoride) on sound and demineralized bovine enamel surfaces. Specimens were randomly assigned to different treatments that included daily pH cycling and brushing three times a day with one of the following dentifrices (n = 8): Neutraçucar (arginine and fluoride), Colgate Total 12 (fluoride) and My First Colgate (no fluoride). Enamel carious lesions were artificially created one week before the beginning of these treatments (demineralized bovine enamel (DE) groups). The same groups were also tested in sound enamel (sound bovine enamel (SE) groups). Microhardness was measured at baseline and after one, two, and five weeks of treatment using a Knoop indenter. Statistical analysis involved two-way Analysis of Variance (ANOVA) and Tukey’s test. After five weeks, both Total 12 and Neutraçucar had increased the microhardness of DE specimens (p < 0.05). Only Neutraçucar had increased the microhardness of the sound enamel after five weeks of treatment. Thus, it could be concluded that arginine-based dentifrices increase the microhardness of sound and demineralized bovine enamel surfaces.